ANALYSIS OF TEACHER NEEDS RELATED TO E-LEARNING SCHOOLOGY CONTENT IN CREATIVE WRITING IN MIDDLE SCHOOLS THROUGHOUT PALEMBANG CITY - Ernalida Ernalida; Santi Oktarina; Rizki Turama (University of Kuningan, 2021)
Learning Indonesian in the text-based 2013 curriculum directs students to be able to produce text-based writings. However, the ability of students to write creatively in middle school found in the field is still in the weak category. Obstacles related to this are increasing considering that Indonesia is currently experiencing the Covid 19 pandemic which requires learning to be carried out from home so that supporting learning media is needed in accordance with existing conditions. Based on the above, a solution is needed to overcome this, one of which is the use of E-Learning Schoology, which is learning that is in accordance with the character of generation Z. This research aimed to determine the needs of teachers regarding E-Learning Schoology content in learning creative writing in secondary schools in Palembang city. This research is a type of research and development. The research object was Indonesian language teachers in SMA in Palembang city. The data collection method used is a survey method with a questionnaire. Data are analyzed quantitatively and qualitatively. The results of the study show that when viewed in terms of necessities, the content of E-Learning Schoology in learning creative writing in secondary schools in Palembang must be adjusted to the principles of learning to write, the principles of electronic / online learning, the Circular of the Minister of Education and Culture No.4 of 2020 concerning Implementation of Education Policies in an Emergency Period of the Spread of Corona Virus Disease (COVID 19) and distance learning guides for teachers during schools closed due to the Covid-19 pandemic. The next finding is that when viewed from the components that are needed, teachers really need E-Learning Schoology in learning creative writing at high schools in Palembang. The last finding is that there are still deficiencies in the implementation of learning creative writing and the media used in secondary schools in Palembang is not adequate yet.